Resource at risk Philippine coral reefs. (Bookmark Video and Moving Images, 1998)
This video documentary tackles the vital issue of coral reef destruction in the Philippines. Coral reefs are one of our most precious resources. They are to the sea what forest are to the land. One square kilometer of healthy reef can produce up to 30 metric tons of fish a year. More than 50% of the Filipino people depend on the sea for their main source of protein.